Natural and Synthetic 6-Aryl Pyrones. An Unexpected Reaction of Dihydropyrones with NBS Leads to the First Synthesis of Allantopyrone C - Podolak, Kyle; Kraus, George A. (Synthesis, 2022)
Nigerapyrone A, aloenin aglycone, 4′-methyl klavuzon, and allantopyrone C were synthesized from commercially available aldehydes.
Keywords: pyrones; N-bromosuccinimide; total synthesis; nigerapyrone; allantopyrone